High-density and low-density gas diffusion layers for proton exchange membrane fuel cells: Comparison of mechanical and transport properties - Xiao, Liusheng; Bian, Miaoqi; Zhu, Lijun; Duan, Kangjun; Leng, Wenliang; Zeis, Roswitha; Sui, Pang Chieh; Zhang, Houcheng (International Journal of Hydrogen Energy, 2022)
Gas diffusion layers (GDL) play multi-roles in proton exchange membrane fuel cells, including gas-water transport, thermal-electron conduction and mechanical support. Mechanical strength and transport properties are essential for GDLs. In this work, high-density (paper-type) and low density (felt-type) GDLs are scanned and reconstructed using X-ray computed tomography. Porosities under different compression ratios are compared and discussed. Effective diffusivity and liquid water permeability are calculated using pore-scale modeling and lattice Boltzmann method. Mechanical strength, anisotropic thermal-electrical resistivity for two types of GDLs are obtained using compression tests and thermal-electrical conductivity measurements. Results show that the porosity, diffusivity, permeability, and through-plane thermal-electrical conductivity of felt-type GDL are significantly higher than that of paper-type GDL owing to the higher porosity and fiber-clusters oriented along the through-plane direction. The in-plane electrical resistivity of paper-type GDL is lower than that of felt-type GDL. The mechanical strength of felt-type GDL is much lower, but the fibers of paper-type GDL are more easily to be broken because of its lower elasticity. The results obtained may guide microstructure optimization and performance improvement of GDLs.
CRIS-Team Scopus Importer:2023-08-01
Keywords: Conductivity measurement; Felt-type GDL; Lattice Boltzmann method; Paper-type GDL; Pore-scale modeling; X-ray computed tomography